MEUF for removal and recovery of valuable organic components present in effluents: A process intensified technology. (8th August 2022) - Das, Pallabi; Sharma, Ankita; Singh, Yash; Upadhyay, Sidhidatri; Verma, Shikha
Abstract: In recent years, the domain of the research space in novel separation process has been led by membrane systems as a panacea providing multifarious benefits of high separation efficiency, elimination of extreme process conditions, sustainability, and environment friendliness coupled with high operational flexibility. In this niche area, often, ultrafiltration is touted as a robust separation technique due to its high separation efficiency, membrane stability, and lower operating costs. The only drawback of relatively large pore size can be overcome by combining surfactant addition, leading to development of integrated processes termed as Micellar Enhanced Ultrafiltration. MEUF processes isolate and selectively separate valuable organics present in effluent streams. The process characteristics fit the bill as a typified example for process intensification Technology interventions for recycling of surfactants can enhance the cost‐competitiveness of the process. This has the potential to develop into a broad‐spectrum effluent treatment option with a change of surfactants for target contaminants. Here, in this review, we attempt to critically examine the unique features of this technology, development of spin‐offs with wide‐ranging applications. Specifically applications in removal of hazardous, and persistent components like dissolved organics have been critically studied. The focus was to highlight the crux of the novel technologies highlighting the efficacy and the underlying concept of process intensification. Practitioner Points: Role of MEUF as a sustainable process intensifying separation technique for removal and recovery of organics. Novel process development using MEUF. Comparative performance analysis to assess efficacy. Discussions on future integrative process development. Sustainability aspect of MEUF with possibility of byproduct recovery. Abstract : Novel process development using MEUF : process intensifying technique for removal and recovery of organics. Comparative performance analysis to assess efficacy and Cost‐benefit analysis and trade‐offs to consider for MEUF operation